Influencia de la resistencia del suelo mejorado en el diseño de losa de cimentación mediante un modelo de interacción suelo – estructura - Marin Bardales, Noe Humberto (2021)
The increase in constructions has generated that buildings are built on soft soil spaces, where the value of their resistance is low; causing problems of a structural nature. For this, engineering professionals generally propose the construction of foundation slabs, placed on a compacted improved soil (granular material). This technique manages to increase the resistance of the stratum above the resistance of the natural soil, but this value is not considered in the design of the foundation, nor its influence on the structure. Within this, the study problem is: How does the resistance of the improved soil influence the design of the foundation slab through a soil-structure interaction model? Where the objectives are: To capture the geotechnical characteristics of the improved soil of the quarries under study. Capture the geotechnical characteristics of the natural soil of the building to be analyzed. Calculate the strength of the improved soil. Determine the influence of the improved soil on the design of the foundation under the soil-structure interaction model of D.D.Barkan-O.A.Savinov, A.E.Sargsian and N.G.Shariya. The research design is experimental of an explanatory type. The research technique is observation and documentary review. The research concludes that the granular material from the “Racarrumi” quarry increases the design resistance by 30.54% with a 65 cm height of added layer. Then the soil-structure interaction model N.G. Shariya shows the influence of the improved soil on the foundation slab and its structural behavior.